Adhesive and its manufacturing method

The adhesive composition addresses the need for primerless adhesion in plastic components by using gas-rich dry processing conditions, achieving superior bonding strength and durability without interfacial failure.

JP7611637B2Active Publication Date: 2025-01-10SIKA TECH AG
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021129992
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-06
Publication Date
2025-01-10
Estimated Expiration
2041-08-06

AI Technical Summary

Technical Problem

Existing adhesives for bonding plastic components in automobiles require a primer for effective adhesion, increasing the number of work steps and not fully addressing the adhesion demands of modern resin components.

Method used

An adhesive composition that adheres to resin members without a primer, utilizing frame-treated members and specific gas-rich conditions during dry processing to enhance adhesion, with a volume ratio of air and combustion gas within a defined range to optimize wetting tension and reduce molecular scission.

Benefits of technology

The adhesive exhibits excellent adhesion properties without a primer, improving bonding strength and reducing the risk of interfacial failure by minimizing molecular scission and surface brittleness, thereby enhancing the durability of plastic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611637000007
    Figure 0007611637000007
  • Figure 0007611637000008
    Figure 0007611637000008
  • Figure 0007611637000009
    Figure 0007611637000009
Patent Text Reader

Abstract

To provide an adhesive product and a manufacturing method thereof showing excellent adhesiveness without using a primer.SOLUTION: In an adhesive product, an adhesive agent bonds a first member involving a plastic and having a part flame-treated by the following condition A1 and a second member; the first member bonds with the adhesive agent at the flame-treated part and a primer is not interposed between the first member and the adhesive agent. (Condition A1) A volume ratio RA1 of an air used for generating a flame in the flame treatment and a combustion gas and a volume ratio RP of the air and the combustion gas on complete combustion of the combustion gas satisfy 0.8≤volume ratio RA1 / volume ratio RP≤1.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive article and a method for producing the same. [Background technology]

[0002] Conventionally, steel sheets have been used for interior and exterior components of automobiles, such as the body, front doors, rear doors, tailgates, front bumpers, rear bumpers, and rocker moldings. However, from the viewpoint of reducing the weight of automobiles, the use of plastics such as polypropylene resin for the above interior and exterior components is increasing. When plastics (resins) are used for interior and exterior components of automobiles, a primer is usually applied to the bonding surface of the resin components, and then an adhesive is applied and the components are bonded together. However, in the above case, problems such as an increase in the number of work steps are encountered, and therefore there is a demand for an adhesive composition that has excellent adhesion to resin components without the use of a primer. To date, methods for manufacturing laminated members (e.g., Patent Document 1) and isocyanate-based adhesives (e.g., Patent Document 2) have been proposed that show excellent adhesion to resin members that have been subjected to surface treatments such as dry treatments, even without the use of a primer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-128052 A [Patent Document 2] Patent No. 6756393 Summary of the Invention [Problem to be solved by the invention]

[0004] Recently, there has been a demand for further improvement in the adhesiveness of resin members formed by adhesives used in automobiles. In this situation, the inventors, referring to Patent Documents 1 and 2, produced a bonded product using a frame-treated member and an adhesive without using a primer, and found that there was room for improvement in the adhesiveness.

[0005] In view of the above circumstances, a main object of the present invention is to provide an adherend that exhibits excellent adhesion without the use of a primer.

[0006] Furthermore, the present inventors have found the following two problems in relation to the above object (to provide an adhered article that exhibits excellent adhesion without the use of a primer). One is whether the air-rich conditions that have been used so far in dry processing of plastic substrates are suitable for improving adhesion, and the other is why there are cases in which adhesion is poor even though the wetting tension after dry processing meets the evaluation criteria that have been used to determine good adhesion.

[0007] Usually, the wetting tension of the plastic member after dry processing is confirmed using a mixed liquid (wetting reagent) specified in JIS K6768:1999. It has been said that the higher the wet tension, the higher the wettability to the adhesive, and the better the adhesiveness between the plastic member and the adhesive. For example, the wet tension of a polypropylene-containing substrate before framing is about 28 to 30 mN / m, but a wet tension of about 40 mN / m or more after framing is considered to be a guideline for good adhesiveness.

[0008] Generally, in dry processes such as flame processing, the volume ratio R of the air and combustion gas used to generate the flame is K (Volume ratio R K = air / combustion gas in the generation of flame in dry processing) is the volume ratio R of air to combustion gas when the combustion gas is completely combusted. P (Volume ratio R P The volume ratio R is set to be larger than the ratio of air to combustion gas when the combustion gas is completely burned. K The volume ratio R PThis is because when the framing treatment is performed under air-rich conditions, the wet tension obtained can be made considerably larger than that before the framing treatment. For example, if the substrate contains polypropylene, the wet tension after the framing treatment can be made 40 mN / m or more. In this way, it has traditionally been thought that by performing dry processing (e.g., frame processing; the same applies below) on a plastic substrate in an air-rich state and making the wet tension significantly greater than before the dry processing (e.g., a difference in wet tension before and after frame processing of 10 mN / m or more), the adhesion between the substrate and adhesive after the dry processing is improved.

[0009] However, contrary to the above prediction, the present inventors have found that the adhesiveness between the substrate and the adhesive is not necessarily improved even though the substrate is subjected to dry processing in an air-rich state and the wet tension of the substrate is significantly higher than that before the dry processing. From the above findings, the present inventors have also found the above two problems. [Means for solving the problem]

[0010] As a result of extensive research into the above problem (the provision of an adhesive that exhibits excellent adhesion even without the use of a primer), the inventors have found that the air-rich conditions that have been conventionally used in dry processing of plastic-containing components are not necessarily suitable for improving adhesion, and that the above problem can be solved by performing dry processing under gas-rich or complete combustion of combustion gas conditions (hereinafter also referred to as gas-rich conditions, etc.). Furthermore, in the evaluation of wetting tension using a wetting reagent, which has conventionally been performed to confirm adhesion, it has been found that the increase in wetting tension before and after dry processing does not necessarily correlate with the adhesion between the plastic component and the adhesive. It has also been found that when dry processing of a plastic substrate is performed under conditions such as gas-rich conditions, even if the increase in wetting tension before and after the dry processing is small (for example, the difference in wetting tension before and after frame processing is 8 mN / m or less), the adhesion between the plastic substrate and the adhesive after the dry processing is improved. That is, the present inventors have found that the above problems can be solved by the following configuration.

[0011] [1] The adhesive bonds a first member containing plastic and having a portion that has been framed under the following condition A1 to a second member, The first member is bonded to the adhesive at the framed portion, An adherend in which no primer is interposed between the first member and the adhesive. (Condition A1) The volume ratio R of air and combustion gas used to generate the flame in the above flame treatment A1 and the volume ratio R of air to combustion gas when the combustion gas is completely burned. P and satisfy the following formula (1). 0.8 or less volume ratio R A1 / Volume ratio R P <= 1 (1) [2] The adhesive described in [1], wherein the first member contains a polyolefin resin as the plastic and an inorganic material. [3] The adhesive according to [1] or [2], wherein the adhesive is a urethane adhesive, an epoxy adhesive, a modified silicone adhesive, or an acrylic adhesive. [4] The adhesive article according to any one of [1] to [3], wherein the second member contains plastic, has a portion framed under the following condition A2, and is bonded to the adhesive at the framed portion. (Condition A2) The volume ratio R of air and combustion gas used to generate the flame in the above flame treatment A2 and the volume ratio R of air to combustion gas when the combustion gas is completely burned. P and satisfy the following formula (2). 0.8 or less volume ratio R A2 / Volume ratio R P <= 1 (2) [5] The bonded article according to any one of [1] to [4], wherein the combustion gas contains propane gas or natural gas.

[0012] [6] A surface treatment process in which a frame treatment is performed on a first member containing plastic under the following condition A1; an adhesive application step of applying an adhesive to the first member that has been subjected to the frame treatment without using a primer; a bonding step of bonding a second member to the adhesive to bond the first member, the adhesive, and the second member together. (Condition A1) The volume ratio R of air and combustion gas used to generate the flame in the above flame treatment A1 and the volume ratio R of air to combustion gas when the combustion gas is completely burned. P and satisfy the following formula (1). 0.8 or less volume ratio R A1 / Volume ratio R P <= 1 (1) [7] The second member contains plastic, A surface treatment step is provided in which, prior to the bonding step, the second member is subjected to a frame treatment under the following condition A2: The method for producing a bonded product according to [6], wherein in the bonding step, a second member that has been subjected to the frame treatment is bonded to the adhesive. (Condition A2) The volume ratio R of air and combustion gas used to generate the flame in the above flame treatment A2 and the volume ratio R of air to combustion gas when the combustion gas is completely burned. P and satisfy the following formula (2). 0.8 or less volume ratio R A2 / Volume ratio R P <= 1 (2) Effect of the Invention

[0013] The adhesive of the present invention has excellent adhesion even without the use of a primer. According to the manufacturing method of the present invention, a bonded product exhibiting excellent adhesiveness can be obtained without using a primer. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a schematic cross-sectional view showing the process steps of one embodiment of the production method of the present invention. [Diagram 2] FIG. 2 is a TEM image taken at a magnification of 100,000 times of the cross section of the first member after the frame treatment under the conditions (air rich) shown in Comparative Example 1. [Diagram 3] FIG. 3 shows a TEM image of the cross section of the adhesive layer at a portion visually evaluated as having AF (interfacial failure) after a shear test was conducted under Condition 2 of Comparative Example 1, and the image was taken at a magnification of 100,000 times. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will be described below. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits.

[0016] [Adhesive of the present invention] The adhesive of the present invention is The adhesive bonds a first member containing plastic and having a portion that has been framed under the following condition A1 to a second member, The first member is bonded to the adhesive at the framed portion, The bond is formed without a primer between the first member and the adhesive. (Condition A1) The volume ratio R of air and combustion gas used to generate the flame in the above flame treatment A1 and the volume ratio R of air to combustion gas when the combustion gas is completely burned. P and satisfy the following formula (1). 0.8 or less volume ratio R A1 / Volume ratio R P <= 1 (1)

[0017] It is presumed that the adhesive of the present invention exhibits excellent adhesiveness due to its structure. Although the reason is not clear, it is presumed to be as follows. (Improvement of adhesion by flame treatment under gas-rich conditions, etc.) Conventionally, as described above, in order to increase the difference in wetting tension due to the wetting reagent before and after the dry treatment, the dry treatment has been carried out in an air-rich state relative to the combustion gas, that is, in an atmosphere in which there is more oxygen in the combustion gas than under the conditions of complete combustion of the combustion gas. However, the inventors believe that dry processing under air-rich conditions introduces excessive oxygen atoms to the surface of the plastic member, which makes the surface of the plastic member brittle. In other words, the introduction of excessive oxygen atoms to the surface of the plastic member causes molecular scission of the plastic material on the surface of the plastic member (when the plastic contains polypropylene, the generation of carboxylic acids such as acetic acid, etc.), and when a plastic substrate with such a surface state is bonded to an adhesive and evaluated in a shear test, the plastic substrate will undergo interface failure (interface failure as observed visually (by the naked eye; the same applies below)).

[0018] When the above-mentioned interface failure was observed more closely with a transmission electron microscope (TEM), it was found that the above-mentioned interface failure may include material failure in which a thin layer of the plastic substrate peels off from the surface of the plastic substrate. The above matters will be described below with reference to the attached drawings. Note that the present invention is not limited to the attached drawings. FIG. 2 is a TEM image taken at a magnification of 100,000 times of the cross section of the first member after the frame treatment under the conditions (air rich) shown in Comparative Example 1. 2, a layer 205 can be observed on the surface of the first member 201 after the framing process. The embedding resin 203 is the resin used for preparing the TEM sample. The layer 205 is considered to correspond to a skin layer in which the resin component (mainly polypropylene) of the first member (#4) is ubiquitous on the surface of the first member (#4) after the frame treatment. The thickness of the layer 205 was 30 to 40 nm.

[0019] FIG. 3 shows a TEM image of the cross section of the adhesive layer at a portion visually evaluated as having AF (interfacial failure) after a shear test was conducted under Condition 2 of Comparative Example 1, and the image was taken at a magnification of 100,000 times. In Figure 3, a layer 305 could be observed on the surface of adhesive layer 301. The embedding resin 303 is the resin used for the TEM sample preparation. 2 (skin layer), which was adhered to the adhesive in the shear test and then peeled off together with the adhesive layer 301 in the shear test. The thickness of layer 305 was about 30 nm. In this way, it was confirmed that the portion visually evaluated as having AF (interfacial failure) may, in detail, include failure of a thin layer of material on the surface of the first component. As described above, although the state of failure after the shear test was visually evaluated as AF, the fact that thin-layer material failure on the surface of the first component was observed under magnification proves that dry processing under air-rich conditions embrittles the surface of the plastic component. Since a brittle surface is prone to peeling, in the shear test the embrittled surface peeled off thinly from the plastic component together with the adhesive, and as a result, it is believed that the state of failure after the shear test was visually evaluated as AF, and thin-layer material failure on the surface of the first component was observed under magnification.

[0020] In the present invention, the details of the above-mentioned TEM analysis are as follows. (1) Preparation of TEM samples After frame processing or shear testing, the first member was embedded in resin, and the embedded sample was cut into thin films of approximately 100 to 200 μm thickness using an ultramicrotome (under a freezing atmosphere at -100°C). Heavy metal staining (RuO 4 ) was performed to obtain thin sections (samples). (2)TEM The thin sections prepared as described above were subjected to TEM observation. The details of the TEM analysis equipment and analysis conditions are as follows: [ka]

[0021] On the other hand, in flame treatment under gas-rich conditions, nitrogen is more easily introduced to the surface of the plastic member than under air-rich conditions. It is believed that an increase in the introduction of nitrogen and a decrease in the introduction of oxygen under gas-rich conditions makes it less likely that molecular scission of plastic molecules on the surface of the plastic member will occur than an excessive introduction of oxygen under air-rich conditions.

[0022] (Relationship between increase in wetting tension due to wetting reagent and adhesion) When the introduction of oxygen into the plastic substrate by dry processing is excessive or when the introduction of nitrogen is insufficient, it is believed that the above-mentioned situation can be effectively evaluated using a mixed liquid (wetting reagent) specified in JIS K6768:1999. It is the opinion of the present inventors that the evaluation results using the above-mentioned mixed liquid are not necessarily expected to lead to improved adhesion. This is because, in particular, when the wetting tension after dry processing is much higher than before dry processing, it is predicted that the introduction of oxygen into the plastic substrate is excessive. On the other hand, when the amount of nitrogen introduced into the plastic substrate by dry processing is large or when the amount of oxygen introduced into the plastic substrate is small, it was found to be difficult to find a surface condition or dry processing conditions that provide good adhesion based on the evaluation results of the above-mentioned JIS standard. For example, the wetting tension of a pure polypropylene-based member without surface treatment by a wetting reagent is generally about 28 to 30 mN / m, but the present inventors have found in the present invention that a polypropylene-based member that has been frame-treated under gas-rich conditions or the like does not react to a wetting reagent for evaluation with a wetting tension of 40 mN / m or more (even when a wetting reagent is used, the liquid film of each wetting reagent remains in the state when applied without breaking for 2 seconds or more), yet exhibits excellent adhesion. Based on this, it was thought that the adhesion of the surface of a plastic substrate that has been dry-treated under gas-rich conditions or the like cannot be simply evaluated by a wetting reagent.

[0023] (Complete combustion of combustion gas, air rich, gas rich) In flame processing, propane gas or natural gas, which is mainly composed of methane, is usually used as the combustion gas. The reaction for the complete combustion of propane is: C 3 H 8 +5O 2 →3CO 2 +4H 2 O When propane is completely combusted, the volume ratio R (air / propane) of air to combustion gas (propane) is 23.8 / 1, assuming the oxygen concentration in the air is 81%. From the above, for example, if the air flow rate (flow rate is the flow rate per unit time; same below) is set to 100 L / min in order to completely combust propane, the flow rate of propane will be 4.20 L / min.

[0024] The complete combustion reaction of methane, the main component of natural gas, is as follows: CH 4 +2O 2 →CO 2 +2H 2 O When natural gas is completely combusted, the volume ratio R (air / natural gas) of air to combustion gas (natural gas) is 9.2 / 1, assuming the oxygen concentration in air is 81%. From the above, for example, if the air flow rate is set to 100 L / min in order to completely combust the natural gas, the flow rate of the natural gas will be 10.87 L / min.

[0025] Volume ratio R when the combustion gas is completely burned P In the case of (air / combustion gas), for example, if the air flow rate is fixed and the combustion gas flow rate is increased, the mixture of air and combustion gas becomes gas-rich (combustion gas-rich). The volume ratio R A (Volume ratio R A is the volume ratio of air to combustion gas during flame processing. Hereafter, the volume ratio R A The same applies to the volume ratio R P Smaller, volume ratio R A / Volume ratio R P is less than 1. Conversely, the above volume ratio R PIf the flow rate of the combustion gas is reduced, the mixture of air and combustion gas becomes air-rich. The volume ratio R A is the volume ratio R P Larger, volume ratio R A / Volume ratio R P is greater than 1. The bonded article of the present invention will now be described.

[0026] [First member] In the present invention, the first member is a member containing plastic. When the adhesive product of the present invention is used as an exterior member for an automobile, such as a back door of an automobile, the first member is preferably used as an inner member.

[0027] 〔plastic〕 Preferably, the plastic comprises a crystalline thermoplastic resin. Examples of plastics include polyolefin resins such as polyethylene, polypropylene, and polybutylene; methacrylic resins such as polymethyl methacrylate; polystyrene resins such as polystyrene, ABS, and AS; polyester resins such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate, polyethylene naphthalate (PEN), and poly 1,4-cyclohexyldimethylene terephthalate (PCT); polycaproamide (nylon 6), polyhexamethylene adipamide (nylon 66), polyhexamethylene sebacamide (nylon 610), polyhexamethylene dodecamide (nylon 612), polydodecanamide (nylon 12), polyhexamethylene terephthalamide (nylon 6T), polyhexanemethylene isophthalamide (nylon 6I), polycaproamide / polyhexamethylene terephthalamide copolymer (nylon 6 / 6T), poly ... Examples of the resin include polyamide resins selected from nylon resins and nylon copolymer resins such as poly(nylon 66 / 6T) and poly(nylon 66 / 6I); polyvinyl chloride resins; polyoxymethylene (POM); polycarbonate (PC) resins; polyphenylene sulfide (PPS) resins; modified polyphenylene ether (PPE) resins; polyetherimide (PEI) resins; polysulfone (PSF) resins; polyethersulfone (PES) resins; polyketone resins; polyethernitrile (PEN) resins; polyetherketone (PEK) resins; polyetheretherketone (PEEK) resins; polyetherketoneketone (PEKK) resins; polyimide (PI) resins; polyamideimide (PAI) resins; fluororesins; modified resins obtained by modifying these resins, or mixtures of these resins.

[0028] From the viewpoint of achieving better effects of the present invention, the first member preferably contains a polyolefin resin as a plastic, more preferably contains polyethylene and / or polypropylene, and further preferably contains polypropylene.

[0029] From the viewpoint of obtaining superior effects of the present invention, the content of the plastic in the first member is preferably 10 to 100% by mass, and more preferably 60 to 100% by mass, based on the total amount of the first member.

[0030] (inorganic) In one preferred embodiment, the first component further contains an inorganic substance. Examples of inorganic substances include silica, titanium oxide, magnesium oxide, antimony oxide, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, calcium carbonate, talc, clay, mica, glass fiber, carbon black, graphite, and carbon fiber. From the viewpoint of achieving better effects of the present invention, the inorganic material preferably contains at least one selected from the group consisting of talc, carbon fiber, and glass fiber, more preferably contains talc, and even more preferably contains talc and glass fiber. When the first member further contains an inorganic substance, the content of the inorganic substance in the first member is preferably 5 to 40 mass % of the total amount of the first member, from the viewpoint of achieving better effects of the present invention.

[0031] [Frame Processing] Flame treatment is a type of dry treatment in which the surface of a component is treated with a flame. In the present invention, the first member has a portion that has been frame-treated under the following condition A1 (also referred to as the "specific condition"). (Condition A1) The volume ratio R of air and combustion gas used to generate the flame in the above flame treatment A1 and the volume ratio R of air to combustion gas when the combustion gas is completely burned. P and satisfy the following formula (1). 0.8 or less volume ratio R A1 / Volume ratio RP <= 1 (1)

[0032] (Combustion gas) The combustion gas used in the flame treatment preferably contains propane gas or natural gas. In the present invention, the combustion gas does not contain oxygen in the atmosphere.

[0033] [Volume ratio R A1 〕 In the present invention, the volume ratio R of the air and the combustion gas used to generate the flame in the flame treatment of the first member A1 (Air / combustion gas) can be calculated as the ratio of air flow rate to combustion gas flow rate (air flow rate / combustion gas flow rate). When the combustion gas contains propane, the flow rate of the combustion gas is preferably 4.2 to 5.25 L / min, and more preferably 4.3 to 4.7 L / min, when the air flow rate is 100 L / min, from the viewpoint of achieving better effects of the present invention. When the combustion gas contains natural gas, the flow rate of the combustion gas is preferably 11.0 to 13.5 L / min, and more preferably 11.4 to 12.0 L / min, when the air flow rate is 100 L / min, from the viewpoint of achieving better effects of the present invention.

[0034] [Volume ratio R P 〕 In the present invention, the volume ratio R of air to combustion gas when the combustion gas used to generate a flame in the flame treatment of the first member is completely combusted P can be obtained as a calculated value. When the combustion gas contains propane, the volume ratio R of the air to the combustion gas (propane) when the propane is completely combusted is P As mentioned above, the ratio (air / propane) is 23.8 / 1, assuming the oxygen concentration in the air is 81%. When the combustion gas contains natural gas (mainly methane), the volume ratio R of the air to the combustion gas (natural gas) when the natural gas is completely combusted P The ratio (air / natural gas) is 9.2 / 1, assuming the oxygen concentration in air is 81%.

[0035] [Formula (1)] In the present invention, the following formula (1) is satisfied. 0.8 or less volume ratio R A1 / Volume ratio R P <= 1 (1) Volume ratio R A1 / Volume ratio R P From the viewpoint of obtaining superior effects of the present invention, it is preferable that the ratio is 0.85 to 0.95.

[0036] (Other conditions for framing) Frame Processing Unit The flame treatment device is preferably a device capable of setting the flow rate of air and the flow rate of combustion gas during use.

[0037] The distance between the burner (the tip) of the flame treatment device and the member can be, for example, 10 to 100 mm. In the flame treatment, one preferred embodiment is to apply an oxidizing flame to the surface of the member. The speed at which the burner of the flame treatment device is moved relative to the member can be, for example, 300 to 1000 mm / sec. The number of passes (the number of times the burner is swept) can be, for example, 1 to 5 times. In the present invention, when frame treatment is carried out under specific conditions, excellent adhesion can be obtained and robustness is excellent even if conditions other than the specific conditions in the frame treatment (for example, the conditions described above) are carried out over a wide range as described above.

[0038] The first member may be entirely or partially framed.

[0039] (Wetting tension) As described above, in the present invention, it is not appropriate to simply evaluate the wet tension obtained in accordance with JIS K6768:1999 for the surface of the first member that has been frame-treated under the specified conditions A1 using general evaluation criteria (for example, the wet tension after dry treatment is 40 mN / m or more, or is 10 mN / m or more greater than the wet tension before dry treatment). Hereinafter, the results of frame treatment under specific conditions for the first member are the same when the second member is frame-treated under the specified conditions A2. When the surface condition of the portion of the first member that has been subjected to the frame treatment is confirmed by the wet tension, the wet tension may be, for example, 38 mN / m or less. In the present invention, it has been found that the adhesion is excellent even if the wet tension of the portion of the first member that has been subjected to the frame treatment under the specific conditions is 38 mN / m or less. It has also been found that the wet tension of the portion of the first member that has been subjected to frame treatment under the above specific conditions is preferably 32 to 38 mN / m, and more preferably 32 to 35 mN / m, from the viewpoint of achieving a superior effect of the present invention.

[0040] (Difference in wetting tension before and after frame treatment) From the viewpoint of achieving superior effects of the present invention, the difference in wet tension of the first member before and after the frame treatment is preferably less than 10 mN / m, and more preferably 8 mN / m or less.

[0041] (Introduction of nitrogen atoms) Analysis of the portion of the first member that has been subjected to the flame treatment by X-ray photoelectron spectroscopy (XPS) reveals that the amount of nitrogen atoms in the portion is greater than the amount of nitrogen atoms on the surface of the first member before the flame treatment. Furthermore, the amount of nitrogen atoms on the surface of the first component subjected to flame treatment under specific conditions is greater than the amount of nitrogen atoms on the surface of the component subjected to flame treatment under conditions other than the specific conditions, indicating that the introduction of oxygen is appropriate. In the present invention, it is presumed that by carrying out the flame treatment under specific conditions, the amount of nitrogen atoms on the surface of the first component is increased, and embrittlement of the surface of the component due to the introduction of excessive oxygen is suppressed, resulting in improved adhesion.

[0042] [Adhesion between the first member and the adhesive] In the present invention, the first member is bonded to an adhesive, which will be described later, at the portion that has been framed as described above. The bonding area of ​​the first member may be the entirety of the framed portion, or may be a part of it.

[0043] [Second member] The bonded article of the present invention has a second member. The second member is not particularly limited. For example, the second member may be the same as the first member. The second member may be the same as the first member.

[0044] From the viewpoint of obtaining a superior effect of the present invention, it is preferable that the second member contains a plastic. The material of the second member may be the same as that of the first member. From the viewpoint of achieving a better effect of the present invention, it is preferable that the second member has a portion that has been frame-treated under the following condition A2. (Condition A2) The volume ratio R of air and combustion gas used to generate the flame in the above flame treatment A2 and the volume ratio R of air to combustion gas when the combustion gas is completely burned. P and satisfy the following formula (2). 0.8 or less volume ratio R A2 / Volume ratio R P <= 1 (2) Condition A2 can be similar to condition A1. The second member is preferably bonded to an adhesive, which will be described later, at the framed portion as described above. The bonding of the second member to an adhesive at the framed portion can be the same as that described for the first member.

[0045] [glue] The adhesive of the present invention comprises an adhesive. In the present invention, the adhesive bonds the first member and the second member.

[0046] From the viewpoint of achieving superior effects of the present invention, the adhesive is preferably a urethane-based adhesive, an epoxy-based adhesive, a modified silicone-based adhesive, or an acrylic-based adhesive, and more preferably a urethane-based adhesive. The urethane adhesive and the epoxy adhesive are preferably of the one-component or two-component type. An example of a one-liquid type urethane adhesive is a moisture-curing adhesive that contains a urethane prepolymer having an isocyanate group. An example of a two-liquid type urethane adhesive is an adhesive having a base agent containing a urethane prepolymer and a curing agent containing a polyol. Examples of one-liquid epoxy adhesives include room temperature curing or heat curing adhesives that contain a latent curing agent such as ketimine, oxazolidine, or aldimine-based compounds and a liquid epoxy resin. Examples of two-component epoxy resin adhesives include adhesives having a base selected from liquid epoxy resins (e.g., bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD ​​type epoxy resin, novolac type epoxy resin, etc.) and a curing agent (e.g., amine-based curing agents such as chain aliphatic amines, cyclic aliphatic amines, aromatic amines, nitrogen-containing aromatics such as imidazole compounds, etc., amidoamine curing agents, ketimines, etc.). An example of a modified silicone adhesive is an adhesive containing polyoxyalkylene having a hydrolyzable silyl group.

[0047] [Primer] In the present invention, no primer is interposed between the first member and the adhesive, that is, the first member and the adhesive can be directly bonded to each other. The second member and the adhesive may be bonded via a primer. When the second member has a portion that has been frame-treated under the above condition A2, it is preferable that the second member and the adhesive are bonded without a primer.

[0048] (Application) Applications of the adhesive of the present invention include, for example, automobile interior and exterior components such as automobile bodies, front doors, rear doors, back doors, front bumpers, rear bumpers, and rocker moldings.

[0049] [Method of manufacturing the bonded article of the present invention] The following manufacturing method can be used to manufacture the bonded article of the present invention. The method for producing the bonded article of the present invention (the method for producing the bonded article of the present invention) is as follows: A surface treatment process in which a frame treatment is performed on a first member containing plastic under the following condition A1; an adhesive application step of applying an adhesive to the first member that has been subjected to the frame treatment without using a primer; The method for producing a bonded product includes a bonding step of bonding a second member to the adhesive to bond the first member, the adhesive, and the second member. (Condition A1) The volume ratio R of air and combustion gas used to generate the flame in the above flame treatment A1 and the volume ratio R of air to combustion gas when the combustion gas is completely burned. P and satisfy the following formula (1). 0.8 or less volume ratio R A1 / Volume ratio R P <= 1 (1)

[0050] In the method for producing the bonded article of the present invention, the first member, the second member, the adhesive, the frame treatment, the condition A1, the condition A2, etc. are the same as those in the bonded article of the present invention.

[0051] [Surface treatment process] In the present invention, the surface treatment step is a step of performing frame treatment on the first member containing plastic under the above-mentioned condition A1. The first member used in the surface treatment step is a first member containing plastic (a first member before frame treatment).

[0052] [Adhesive application step] In the present invention, the adhesive applying step is a step of applying an adhesive, without a primer, to the first member that has been subjected to frame treatment in the surface treatment step.

[0053] (Method of applying adhesive) The method of applying adhesive to the first member that has been subjected to the frame treatment is not particularly limited, and examples thereof include a dip coating method, a double roll coater, a slit coater, an air knife coater, a wire bar coater, a slide hopper, a spray coating, a blade coater, a doctor coater, a squeeze coater, a reverse roll coater, a transfer roll coater, an extrusion coater, a curtain coater, a dip coater, a die coater, a coating method using a gravure roll, a screen printing method, a dip coating method, a spray application method, a spin coating method, and an inkjet method.

[0054] [Adhesion process] In the present invention, this is a step of attaching a second member to the adhesive, thereby bonding the first member, the adhesive, and the second member.

[0055] In the bonding step, the method for bonding the second member to the adhesive is not particularly limited. After the second member is attached to the adhesive, the second member may be pressed against the adhesive. In order to harden the adhesive, after the second member is attached, it may be left to cure under room temperature conditions (for example, about 15 to 30° C.). Furthermore, in order to harden the adhesive, heating or the like may be performed after the second member is attached.

[0056] From the viewpoint of obtaining a more excellent effect of the present invention, the second member contains plastic, A surface treatment step is provided in which, prior to the bonding step, the second member is subjected to a frame treatment under the following condition A2: In the bonding step, it is preferable to bond the second member that has been subjected to the frame treatment to the adhesive. The second member can be the same member as the first member. (Condition A2) The volume ratio R of air and combustion gas used to generate the flame in the above flame treatment A2 and the volume ratio R of air to combustion gas when the combustion gas is completely burned. P and satisfy the following formula (2). 0.8 or less volume ratio R A2 / Volume ratio R P <= 1 (2)

[0057] The manufacturing method of the present invention will be described with reference to the drawings. FIG. 1 is a schematic cross-sectional view showing the process steps of one embodiment of the production method of the present invention. FIG. 1(a) shows a first member 10 used in a surface treatment process. First, in a surface treatment step, a frame treatment is performed under specific conditions on the surface 10a of the first member 10. A frame-treated first member 12 is obtained (FIG. 1(b)). Next, in the adhesive applying step, an adhesive 30 is applied to the frame-treated surface 12a of the first member 12 after the frame treatment without using a primer (FIG. 1(c)). Furthermore, in a bonding step, a second member 20 is bonded onto the adhesive 30. An adhesive 32 (a layer formed by curing the adhesive 30) bonds the first member 12 and the second member 20 together to obtain a bonded object 100 (FIG. 1(d)). EXAMPLES

[0058] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0059] <Preparation of adhesive> The components in Table 1 below were mixed using a stirrer in the composition (parts by mass) shown in the table to prepare the base agent shown in the upper row of the table and the curing agent shown in the lower row of the table. Next, 100 g of the prepared base agent and 10 g of the curing agent were mixed together to obtain adhesives 1-2. The adhesive 1 is a urethane adhesive, and the adhesive 2 is an epoxy or modified silicone adhesive.

[0060] [Table 1]

[0061] Details of each component in Table 1 are as follows. (Main ingredient) Polymer 1: Urethane prepolymer synthesized as follows: 700 g of polyoxypropylene diol (average molecular weight 2000), 300 g of polyoxypropylene triol (average molecular weight 3000), and 499 g of 4,4'-diisocyanate phenylmethane (molecular weight 250) were mixed (NCO / OH=2.0 at this time), and 500 g of diisononyl phthalate was added. The mixture was stirred at 80°C for 12 hours in a nitrogen stream to react, synthesizing a urethane prepolymer (polymer 1) containing 2.10% isocyanate groups. Polymer 2: Modified silicone resin whose main chain is polyoxypropylene and has a methyldimethoxysilyl group as a hydrolyzable silyl group at the end. Kaneka MS Polymer S203 (Kaneka Corporation)

[0062] Epoxy resin 1: Adeka Resin EP-4100 (manufactured by Adeka Corporation) Epoxy resin 2: Adeka Resin EP-4006 (manufactured by Adeka Corporation)

[0063] Compound 1: Isocyanurate of hexamethylene diisocyanate (Tolonate HDT, Perstorp) Compound 2: Dimalon (manufactured by Yasuhara Chemical Co., Ltd.) Carbon black: #200MP (manufactured by Shinnikka Carbon Co., Ltd.) Calcium carbonate 1: Super S (manufactured by Maruo Calcium Co., Ltd.) Calcium carbonate 2: Calfine 200 (manufactured by Maruo Calcium Co., Ltd.) Plasticizer 1: Diisononyl phthalate (JPlus) Plasticizer 2: ShellsolTM (Japan Chemtech Co., Ltd.) Catalyst 1: Dimorpholinodiethyl ether (San-Apro)

[0064] (hardening agent) Compound 3: Trifunctional polypropylene polyol (Exenol 1030, Asahi Glass Co., Ltd.) Compound 4: Polybutadiene diol (Poly bd R-45HT, Idemitsu Kosan Co., Ltd., hydroxyl value: 0.8 mol / kg) Compound 5: Terpineol (Yasuhara Chemical Co., Ltd.) Compound 6: 3-glycidoxypropyltrimethoxysilane Silaace S-510 (Chisso Corporation) Compound 7: Vinyltrimethoxysilane KBM 1003 (Shin-Etsu Chemical Co., Ltd.) Compound 8: Ketimine-type latent hardener Epicure H-30 (Mitsubishi Chemical) Calcium carbonate 2: Calfine 200 (manufactured by Maruo Calcium Co., Ltd.) Catalyst 1: Dimorpholinodiethyl ether (San-Apro) Catalyst 2: Tin-based catalyst Neostan U-303 (manufactured by Nitto Kasei Co., Ltd.)

[0065] <Materials> The first and second members used in this example are indicated as "#* / #*" in the "Materials" column of Table 2. In "#* / #*", the first "#*" indicates the number of the material used as the first material. The last "#*" indicates the number of the material used as the second material. Details of members #4 to #7 are as follows. In the following, "GF" stands for glass fiber.

[0066] Material #4: Celanese PP-GF40-0453. Composite material containing at least polypropylene, talc, and glass fiber. Material #4 is black. The glass fiber content of the total composite material is 40% by mass. Wetting tension before flame treatment is 30 mN / m. Material #5: Celanese PP-GF40-0453. Composite material containing at least polypropylene, talc, and glass fiber. Material #5 is gray. The glass fiber content of the total composite material is 40% by mass. Wetting tension before framing is 30 mN / m. - Part #6: A part made of talc-containing PP (talc-containing polypropylene). Obtained by molding TYC1235X manufactured by Lyondell Basell Hifax. Wet tension before frame treatment: 28mN / m Component #7: A component made of CFRTP (carbon fiber reinforced thermoplastic resin). Obtained by molding Toyobo CFRTP product name CTT (carbon fiber content: 50% by volume, fiber direction: in-plane random, matrix resin is polypropylene). Wet tension before frame treatment: 30mN / m

[0067] <<Manufacturing of adhesives>> <Surface treatment process> (Materials, frame treatment or not) The first member (width 25 mm, length 75 mm, thickness 3 mm) and the second member (width 25 mm, length 75 mm, thickness 3 mm) shown in the "Members" column of Table 2 were prepared. The column "Whether each member is framed" in Table 2 indicates whether the first and second members are framed or not.

[0068] (Frame processing conditions A1, A2) One surface of the first member was subjected to frame treatment under the conditions shown in the "Frame treatment conditions A1, A2" column of Table 2. The second member was also subjected to frame treatment under the same conditions. Details of each frame treatment condition are as follows.

[0069] Combustion gas used in conditions A1 and A2: Propane gas (assumed to be 100% propane).

[0070] Flame treatment device 1 used in conditions A1 and A2 (capable of adjusting the flow rate of combustion gas and air) Flame treatment device 1: FTS 201 manufactured by Arcogas. The flame treatment device 1 can adjust the flow rates of the combustion gas and air. The flow rate of the air was fixed at 100 L / min, and the flow rate of the combustion gas was adjusted as follows:

[0071] Gas-rich conditions (Example) When the flame processing apparatus 1 was used in the flame processing, the flow rate of the air was 100 L / min, and the flow rate of the combustion gas (propane) was 4.6 L / min. The volume ratio R A1 (Air / propane) is 21.7 / 1, and the volume ratio R for the complete combustion reaction of propane is P (Air / propane) is 23.8 / 1, so the volume ratio R A1 / Volume ratio R P = 0.91. Volume ratio R A2 , volume ratio R A2 / Volume ratio R P is the above volume ratio R A1 , volume ratio R A1 / Volume ratio R P are similar to

[0072] Air-rich conditions (comparison example) When the flame processing device 1 was used in the flame processing, the flow rate of the air was 100 L / min, and the flow rate of the combustion gas (propane) was 3.7 L / min. The volume ratio R A1 (Air / propane) is 27.0 / 1, and the volume ratio R for the complete combustion reaction of propane P (Air / propane) is 23.8 / 1, so the volume ratio R A1 / Volume ratio R P = 1.14. Volume ratio R A2 , volume ratio R A2 / Volume ratio R P is the same as above.

[0073] Flame treatment device 2, 3 used in conditions A1 and A2 (capable of adjusting the flow rate of combustion gas) The flame processing devices 2 and 3 can adjust the flow rate of the combustion gas, but the air flow rate is unknown and cannot be adjusted. When the flame processing devices 2 and 3 are used, the air / gas ratio cannot be adjusted by the air flow rate. Flame processing device 2: A gas cylinder (Prince Gas Torch Cylinder GT-5000, manufactured by Prince Gas Co., Ltd.; the same applies below) set in a regulator (manufactured by Time Auto Machine Co., Ltd.) that can adjust the gas pressure (fuel gas pressure). The gas pressure is 2 MPa. The tip of the burner is circular, and its inner diameter is 6 mm. Flame processing device 3: A gas cylinder (similar to the GT-5000 above) set in a regulator (similar to the above) that can adjust the gas pressure. The gas pressure is 0.04 MPa. The tip of the burner is fan-shaped, with an arc width of 25 mm and a central angle of 135°.

[0074] Distance between burner and material of flame treatment device under conditions A1 and A2: Select from 20 to 50 mm - Flame treatment device burner movement speed: selectable from 400~800mm / sec Common matters for conditions A1 and A2 In both the present embodiment and the comparative example, the oxidizing flame of the flame was applied to the surface of the component during the flame treatment, and the number of passes of the flame treatment device (the number of times the burner was swept) was one.

[0075] ··Wetting tension of each member after frame treatment: Wetting tension was measured in accordance with JIS K6768:1999 using a wetting tension test mixture manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. as a wetting reagent.

[0076] (Adhesive application process) Next, either Adhesive 1 or Adhesive 2 described in the "Adhesive" column of Table 2 was applied directly to the frame-treated surface of the first member (see Table 1 for Adhesives 1 and 2). No primer was used in the adhesive application step.

[0077] (Adhesion process) The frame-treated portion of the second member was attached to the adhesive so that the first member and the second member formed a single lap joint, and the bonded specimen was then placed under pressure at 23°C and 50% relative humidity for 3 days to cure. The bonded specimen had the first member and the second member bonded together with the adhesive (1.5 mm thick). The bonded area was 25 mm x 25 mm.

[0078] <Evaluation of Adhesion> Shear Test For each bonded product (five samples for each product) produced as described above, a shear test (tensile speed 5.1 cm / min) was carried out according to JIS K6850-1999 under the following conditions to measure the shear strength and visually observe the state of failure and the area ratio (in %) of each bonded product. The results of the average shear strength, minimum shear strength, and the average state of failure observed visually are shown in Table 2.

[0079] (Shear test conditions) Condition 1. A shear test was carried out under heated (121°C) conditions. Condition 2: After heat aging (exposing in air at 80°C for 250 hours), a shear test was carried out at room temperature (23°C, 60% RH). Condition 3: After the environmental test (16 hours at -30°C, followed by 8 hours at 80°C, this cycle was repeated 10 times), a shear test was conducted at room temperature (23°C, 60% RH).

[0080] (Destroyed state) ·CF: Cohesive failure of adhesive AF: Interfacial failure between adhesive and component (Note that visual AF may include material failure in thin layers of components that cannot be confirmed by the naked eye, as mentioned above, but the average failure state results shown in Table 2 are the results of visual observation.) SF: Material failure of the component at the adhesive joint (including at least thin layer material failure that can be confirmed by visual inspection) SF-FMB: Material failure in parts of components that are separated from the adhesive bond The numbers following the alphabetic symbols indicating the failure states indicate the percentage (%) of the area occupied by each failure state in the bonded region.

[0081] Adhesion evaluation criteria In the present invention, in all of the evaluation results of the shear tests under conditions 1 to 3, when the sum of the area occupied by CF and the area occupied by SF and SF-FMB was 100% (i.e., there was no AF), the adhesion was evaluated as excellent. When there was no AF in any of the evaluation results of the shear tests under conditions 1 to 3 and the following conditions were satisfied, the adhesiveness was evaluated as being superior.

[0082] The average shear strength under condition 1 was 1.0 MPa or more. The average shear strength under condition 2 was 3.0 MPa or more (or 4.0 MPa or more), and At least one of the following conditions is satisfied: the average shear strength under condition 3 is 3.0 MPa or more (or 4.0 MPa or more).

[0083] On the other hand, when AF was observed in any of the evaluation results of the shear tests under conditions 1 to 3, the adhesion was evaluated as poor.

[0084] [Table 2]

[0085] [Table 3]

[0086] [Table 4]

[0087] From the results shown in Table 2, Comparative Examples 1 to 10, in which the frame treatment was carried out under conditions other than the specific conditions, had poor adhesion.

[0088] On the other hand, the bonded article of this example, which was subjected to frame treatment under specific conditions, showed excellent adhesion even without the use of a primer. From the above, the bonded article of the present invention has excellent adhesion even without the use of a primer.

[0089] Here, the inventors analyzed the surfaces of the members after the frame treatment in Example 4 and Comparative Example 9 by X-ray photoelectron spectroscopy (also called XPS or ESCA). The conditions for the above analysis are as follows. The results are shown in Table 3. (X-ray photoelectron spectroscopy analysis conditions) Equipment: AXIS-NOVA (KRATOS) X-ray source: Monochromatic AIKa ·Analysis area: 700μm×300μmm

[0090] [Table 5]

[0091] From Table 3, the elemental analysis of Comparative Example 9 showed that there was a lot of oxygen, and the analysis of the C1s peak showed that the peak area of ​​the pk5 portion was large. From the above pk5 results, it can be seen that the surface of the member flame-treated under air-rich conditions was excessively oxidized. Also, referring to the results of Comparative Example 9 in Table 2, AF was observed in the average fracture state under conditions 1 and 2. From the above results of adhesion and XPS of Comparative Example 9, it is considered that the surface of the member flame-treated under air-rich conditions was excessively oxidized, and may have become weakened due to the influence of the scission of plastic molecules caused by this.

[0092] On the other hand, the XPS of Example 4 showed more nitrogen and less oxygen in the elemental analysis than Comparative Example 9. In addition, the peak area of ​​the pk5 portion of the C1s peak was smaller. From the above results, it can be seen that the surface of the member that was flame-treated under gas-rich conditions had a large amount of nitrogen atoms introduced, and therefore had many nitrogen-containing functional groups generated by the introduction of nitrogen atoms, and that oxidation was not excessive. Also, referring to the results of Example 4 in Table 2, there was no AF in the average fracture state under any of conditions 1, 2, and 3, and Example 4 had excellent adhesion. From the results of adhesion and XPS of Example 4, it is considered that the surface of the member that was flame-treated under gas-rich conditions, etc., is difficult to cut plastic molecules due to the introduction of nitrogen atoms, while oxidation proceeds moderately, so that the weakening of the member surface is suppressed. In addition, even if the plastic molecules are cut by excessive oxidation, it is considered that the carboxylic acid generated by the above-mentioned cutting can react with the nitrogen-containing functional group, and the above-mentioned cutting can be restored. Furthermore, by having a large number of nitrogen-containing functional groups, the reactivity with the adhesive is increased. From the above viewpoints, it is believed that in the present invention, an adhesive exhibiting excellent adhesion to members can be obtained without using a primer on the members. The above mechanism is a conjecture of the present inventors, and the mechanism of the present invention is not limited to the above.

[0093] Furthermore, according to the manufacturing method of the present invention, a bonded product exhibiting excellent adhesiveness can be obtained without using a primer. Furthermore, with regard to the manufacturing method of the present invention, from the results of the above examples, it can be said that in dry processing such as flame processing, gas-rich conditions are superior to air-rich conditions in terms of robustness (wider tolerance range, smaller variation, etc.) of surface processing conditions (e.g., the distance between the burner of the flame processing apparatus and the component, the speed at which the burner of the flame processing apparatus is moved, and the type of component used) that can ensure adhesive performance. [Explanation of symbols]

[0094] 10, 12 First member 10a, 12a Surface of the first member 20 Second member 30. Glue 32 Adhesive 100 Glue 201 First member 203, 303 Buried resin 205, 305 layers 301 Adhesive layer

Claims

1. The adhesive bonds a first member having a portion that contains plastic and has been flame-treated under the following condition A1 (excluding flame treatment using a reducing flame), to a second member; The first member is bonded to the adhesive at the framed portion, the adhesive comprises a urethane adhesive, The first member includes a polyolefin resin as the plastic and an inorganic substance, An adhesive comprising: a first member and an adhesive; and a second member and an adhesive bonded to the first member. (Condition A1) In the flame treatment, a flame treatment device capable of adjusting the flow rate of the combustion gas and air is used, and the volume ratio R of the flow rate of the air to the flow rate of the combustion gas by the flame treatment device is A1 and the volume ratio R of air to combustion gas when the combustion gas is completely combusted. P But, The following formula (1) is satisfied. 0.8≦Volume ratio R A1 / Volume ratio R P ≦1 (1)

2. 2. The adhesive according to claim 1, wherein the second member contains a plastic, the second member contains a polyolefin resin as the plastic and an inorganic substance, and has a portion that has been flame-treated (excluding flame treatment using a reducing flame) under the following condition A2, and the adhesive is bonded to the frame-treated portion. (Condition A2) In the flame treatment, a flame treatment device capable of adjusting the flow rate of the combustion gas and air is used, and the volume ratio R of the flow rate of the air to the flow rate of the combustion gas by the flame treatment device is A2 and the volume ratio R of air to combustion gas when the combustion gas is completely combusted. P But, The following formula (2) is satisfied. 0.8≦Volume ratio R A2 / Volume ratio R P ≦1 (2)

3. 3. The adhesive of claim 1 or 2, wherein the combustion gas comprises propane gas or natural gas.

4. A surface treatment step of subjecting a first member containing plastic to a flame treatment (excluding a flame treatment using a reducing flame) under the following condition A1; an adhesive application step of applying an adhesive to the first member that has been subjected to the frame treatment without using a primer; a bonding step of bonding a second member to the adhesive to bond the first member, the adhesive, and the second member; the adhesive comprises a urethane adhesive, The method for manufacturing an adhesive, wherein the first member contains a polyolefin resin as the plastic and an inorganic substance. (Condition A1) In the flame treatment, a flame treatment device capable of adjusting the flow rate of the combustion gas and air is used, and the volume ratio R of the flow rate of the air to the flow rate of the combustion gas by the flame treatment device is A1 and the volume ratio R of air to combustion gas when the combustion gas is completely combusted. P But, The following formula (1) is satisfied. 0.8≦Volume ratio R A1 / Volume ratio R P ≦1 (1)

5. The second member contains a plastic, and the second member contains a polyolefin-based resin as the plastic and an inorganic substance, A surface treatment step is provided in which, prior to the bonding step, the second member is subjected to a flame treatment (excluding a flame treatment using a reducing flame) under the following condition A2: The method for producing a bonded product according to claim 4 , wherein in the bonding step, a second member that has been subjected to the framing process is bonded to the adhesive. (Condition A2) In the flame treatment, a flame treatment device capable of adjusting the flow rate of the combustion gas and air is used, and the volume ratio R of the flow rate of the air to the flow rate of the combustion gas by the flame treatment device is A2 and the volume ratio R of air to combustion gas when the combustion gas is completely combusted. P But, The following formula (2) is satisfied. 0.8≦Volume ratio R A2 / Volume ratio R P ≦1 (2)

Citation Information

Patent Citations

  • Polarizing plate having reflecting function

    JP2000227521A

  • Polarizing plate and method for manufacturing the same

    JP2005284246A

  • Polarizing plate and method of manufacturing the same

    JP2010256909A

  • Method for producing laminated member

    JP2017128052A

  • Manufacturing method for laminate member

    JP2019214188A